Methicillin Resistant Staphylococcus aureus Transmission in a Ghanaian Burn Unit: The Importance of Active Surveillance in Resource-Limited Settings - Amissah, Nana Ama; Buultjens, Andrew H.; Ablordey, Anthony; van Dam, Lieke; Opoku-Ware, Ampomah; Baines, Sarah L.; Bulach, Dieter; Tetteh, Caitlin S.; Prah, Isaac; van der Werf, Tjip S.; Friedrich, Alexander W.; Seemann, Torsten; et al. (Frontiers in Microbiology, 2017)
Objectives: Staphylococcus aureus infections in burn patients can lead to serious complications and death. The frequency of S. aureus infection is high in low- and middle-income countries presumably due to limited resources, misuse of antibiotics and poor infection control. The objective of the present study was to apply population genomics to precisely define, for the first time, the transmission of antibiotic resistant S. aureus in a resource-limited setting in sub-Saharan Africa. Methods: S. aureus surveillance was performed amongst burn patients and healthcare workers during a seven-months survey within the burn unit of the Korle Bu Teaching Hospital in Ghana. Results: 66 S. aureus isolates (59 colonizing and 7 clinical) were obtained from 31 patients and 10 healthcare workers. 21 of these isolates were ST250-IV methicillin-resistant S. aureus (MRSA). Notably, 25 (81%) of the 31 patients carried or were infected with S. aureus within 24 hours of admission. Genome comparisons revealed six distinct S. aureus clones circulating in the burn unit, and demonstrated multiple transmission events between patients and healthcare workers. Further, the collected S. aureus isolates exhibited a wide range of genotypic resistances to antibiotics, including trimethoprim (21%), aminoglycosides (33%), oxacillin (33%), chloramphenicol (50%), tetracycline (59%) and fluoroquinolones (100%). Conclusion: Population genomics uncovered multiple transmission events of S. aureus, especially MRSA, within the investigated burn unit. Our findings highlight lapses in infection control and prevention, and underscore the great importance of active surveillance to protect burn victims against multi-drug resistant pathogens in resource-limited settings.